2000
DOI: 10.1007/pl00008477
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein expression in epithelial ovarian cancer: effect of chemotherapy and prognostic significance

Abstract: These data do not support the hypothesis that metallothionein expression is a determinant of response in ovarian cancer. There is some preliminary evidence from the study of paired samples which indicates that cytotoxic chemotherapy may increase metallothionein expression. An increase in metallothionein was also seen in the study using unmatched biopsies although this did not attain statistical significance, due in part to the large inter-patient variability in expression of this protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
2
13
0
Order By: Relevance
“…We have noted also that in samples obtained after chemotherapy (secondary cytoreductions), MT expression has been significantly higher than in samples originating from the period before chemotherapy (primary laparotomies) [14]. The data on the relationship between MT expression in ovarian cancer and survival of patients treated with platinum-containing drugs are divergent, with some investigators noting the relationship and the other failing to detect it [12][13][14]16].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We have noted also that in samples obtained after chemotherapy (secondary cytoreductions), MT expression has been significantly higher than in samples originating from the period before chemotherapy (primary laparotomies) [14]. The data on the relationship between MT expression in ovarian cancer and survival of patients treated with platinum-containing drugs are divergent, with some investigators noting the relationship and the other failing to detect it [12][13][14]16].…”
Section: Discussionmentioning
confidence: 93%
“…The relationship between MT expression and resistance to platinum-containing drugs is used to be explained by the potential of MT to bind molecules of the drug [6]. Data on predictive value of immunohistochemical estimation of MT have been divergent [12,13,16].…”
Section: Introductionmentioning
confidence: 99%
“…Almost all methods used for detection of metallothionein in tissues are based on immunohistochemical principles [27,59,61,64]. These procedures require biopsy tissues and labor and time consuming sample handling and can not be used for exact quantification of the protein of interest.…”
Section: Electroanalytical Methods In Metallothionein Analysismentioning
confidence: 99%
“…On the other hand, in vitro studies suggested participation of the proteins in detoxication of the tumor cells from platinum-containing compounds [5,12,32]. Moreover, expression of MT and GST-pi has not been analyzed in ovarian cancer samples originating from first-look laparotomies (FLLs) and second-look laparotomies (SLLs) in the same patients.…”
Section: Introductionmentioning
confidence: 93%